Cdk1 and Plk1 mediate a CLASP2 phospho-switch that stabilizes kinetochore–microtubule attachments - Maia, Ana R.R. (The Rockefeller University Press, 2012)
Accurate chromosome segregation during mitosis relies on a dynamic kinetochore (KT)–microtubule (MT) interface that switches from a labile to a stable condition in response to correct MT attachments. This transition is essential to satisfy the spindle-assembly checkpoint (SAC) and couple MT-generated force with chromosome movements, but the underlying regulatory mechanism remains unclear. In this study, we show that during mitosis the MT- and KT-associated protein CLASP2 is progressively and distinctively phosphorylated by Cdk1 and Plk1 kinases, concomitant with the establishment of KT–MT attachments. CLASP2 S1234 was phosphorylated by Cdk1, which primed CLASP2 for association with Plk1. Plk1 recruitment to KTs was enhanced by CLASP2 phosphorylation on S1234. This was specifically required to stabilize KT–MT attachments important for chromosome alignment and to coordinate KT and non-KT MT dynamics necessary to maintain spindle bipolarity. CLASP2 C-terminal phosphorylation by Plk1 was also required for chromosome alignment and timely satisfaction of the SAC. We propose that Cdk1 and Plk1 mediate a fine CLASP2 “phospho-switch” that temporally regulates KT–MT attachment stability.